Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1038/sc.2014.185
|View full text |Cite
|
Sign up to set email alerts
|

MiR-200c regulates ROS-induced apoptosis in murine BV-2 cells by targeting FAP-1

Abstract: Objective: Reactive oxygen species (ROS) are significantly upregulated after spinal cord injury (SCI). MicroRNAs (miRNAs) are reported to be widely involved in regulating gene expression. This paper aims to explore the correlation between ROS-induced cell apoptosis and abnormal miRNA expression after SCI. Methods: To profile the expression of miRNAs after SCI, miRNA microarray was applied and the result was verified by reverse transcription quantitative PCR (RT-qPCR). ROS production following H 2 O 2 stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…In fact, miR-200 regulates neuronal differentiation in the developing olfactory bulb, an effect that is mediated by inhibition of the zinc finger protein Zeb2 (Beclin et al, 2016). Previous research has shown that miR-200c expression is increased in the adult rodent spinal cord following injury (Yu et al, 2014), in the adult cerebral cortex following ischemic preconditioning (Lee et al, 2010), and following cerebrovascular stroke (Stary et al, 2015). These data suggest that miR-200c may be generally elevated during episodes of brain stress, and further suggest that developmental ethanol exposure may function as a persistent source of brain stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, miR-200 regulates neuronal differentiation in the developing olfactory bulb, an effect that is mediated by inhibition of the zinc finger protein Zeb2 (Beclin et al, 2016). Previous research has shown that miR-200c expression is increased in the adult rodent spinal cord following injury (Yu et al, 2014), in the adult cerebral cortex following ischemic preconditioning (Lee et al, 2010), and following cerebrovascular stroke (Stary et al, 2015). These data suggest that miR-200c may be generally elevated during episodes of brain stress, and further suggest that developmental ethanol exposure may function as a persistent source of brain stress.…”
Section: Discussionmentioning
confidence: 99%
“…The implications of elevated miR-200c are unclear however. Although data from cell culture models show that miR-200c overexpression can improve survival in microglia (Yu et al, 2014) and neuroblastoma cells following oxygen glucose deprivation (Lee et al, 2010), studies in whole animal models show that elevated levels of brain miR-200c contribute to the severity of brain damage (Stary et al, 2015). It remains to be determined whether the persistent increase in miR-200c in the juvenile hippocampus represents ongoing damage due to developmental ethanol exposure, adaptive neuroprotection, or persistence of aberrant developmental neurogenic programs.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence of PTEN-3 -UTR was predicted to contain a potential binding site that could be specifically targeted by miR-92a-3p ( Figure 3A). As BV-2 cells share numerous features with primary microglia, the cells were selected for luciferase reporter assay to further confirm the association between PTEN and miR-92a-3p [25]. Two types of luciferase vectors containing wild-type and mutant 3 -UTR of PTEN were constructed, as shown in Figure 3B, miR-92a-3p obviously inhibited the luciferase activity of PTEN-WT vectors, but it did not affect PTEN-MUT vectors (P<0.01, Figure 3B).…”
Section: Mir-92a-3p Was Predicted To Specifically Target Ptenmentioning
confidence: 99%
“…Apoptosis is a major mechanism of neural cell dismissal during the secondary damage of SCI [2]. This cell death process has been described to be induced by either downregulation of miRNAs aiming at pro-apoptotic genes, such as miR29b and the BH3 genes or upregulation of miRNAs that target antiapoptotic genes, such as miR200c and FAP1 [53]. mir-138-5p's target BAK is a member of the BCL2 20 protein family that contributes to the activation of apoptosis through the permeabilization of the mitochondrial outer membrane to release apoptogenic factors, including cytochrome c [40].…”
Section: Discussionmentioning
confidence: 99%